Performance analysis of spectral/spatial of OCDMA system using 2D hybrid ZCC/MD code - Rima. Matem; S. A. Aljunid; M. N. Junita; C.B.M Rashidi; Israa Shihab Aqrab (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper proposes a new spectral/spatial code for Spectral Amplitude Coding in Optical Coding Division Multiple Access (SAC-OCDMA) called two-Dimensional hybrid ZCC/MD code. The new code combines two of the one –dimensional codes which are Zero Cross Correlation (1D ZCC) and Multi-Diagonal code (1D MD). Moreover, it produces a zero cross correlation property for each code. The main goal of this proposed code is to mitigate Phase Induced Intensity Noise and eliminate Multiple Access Interference (MAI). This proposed code can provide a better performance comparing to other codes as 2D FCC/MDW and 2D DPDC according to the obtained numerical analysis.